AWARENESS OF 3D BODY-SCANNING AND PROSPECTIVE UPDATE OF INDONESIAN ANTHROPOMETRY FOR VIRTUAL FASHION DESIGN - Hartono, Markus; Jaya, Brian Kurniawan; Prianka, Dian; Parung, Christabel Annora; Viviany, Viviany (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2023)
It is a challenge for the designer and user in compromising a perfect fit of fashion. This study addresses the awareness of users and development of two different methods for the fitting of a fashion product. The first one, it is an individual anthropometric measurement, whereas the second one is assisted anthropometric measurement. Based on the Focused Group Discussion (FGD), it showed that the virtual fashion technology was perceived as something new and prospective in the future fashion industry. Through the virtual prototyping using CLO3D, it was found that the result had relatively the same as the manual measurement. The virtual one has reduced measurement and lead time significantly. In other words, the virtual measurement is deemed to be a time-saving process, promoting “fitting the product to the user” principle. This study supports a good communication bridge between users and designers through the 3D virtual clothing process, and also contributes to Indonesian anthropometry updates.